Analisis Efektivitas Aplikasi Layanan Online Terintegrasi Warga Makassar (Lontara+) Pemerintah Kota Makassar dalam Meningkatkan Kualitas Pelayanan Publik - M. Rifai Inayatullah (Journal of Management and Creative Business, 2026)
This study aims to analyze the effectiveness of the implementation of Lontara+ in improving the quality of public services in Makassar City. The research employed a qualitative approach using a case study method. Data were collected through observations, in-depth interviews, and documentation involving Regional Government Organizations (Organisasi Perangkat Daerah/OPDs) integrated into the application, as well as members of the public as service users. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which consists of data condensation, data display, and conclusion drawing and verification, supported by source and method triangulation to ensure data validity. The findings indicate that the implementation of Lontara+ has improved service accessibility, service integration, responsiveness, transparency, bureaucratic efficiency, and public participation in the delivery of public services. The integration of various public services into a single application has accelerated service processes and strengthened coordination among OPDs. Nevertheless, the effectiveness of its implementation continues to face several challenges, including limited digital literacy among certain segments of the community, inadequate internet infrastructure, and the need to enhance human resource capacity and organizational culture adaptation. Therefore, continuous efforts to improve application features, strengthen system security, enhance digital infrastructure, and expand public outreach and digital literacy programs are essential to optimize and sustain the quality of digital-based public services.